Numerical Investigation of Hydraulic Fracture Extension Based on the Meshless Method. (17th November 2020) - Zhao, Chaoneng; Hu, Yongquan; Zhao, Jinzhou; Wang, Qiang; He, Pei; Liu, Anbang; Song, Pengju
Abstract : The fracture propagation in hydraulic fracturing is described as a nonlinear problem dynamic boundary. Due to the limitation of mesh refinement, it is difficult to obtain the real crack propagation path using conventional numerical methods. Meshless methods (MMs) are an effective method to eliminate the dependence on the computational grid in the simulation of fracture propagation. In this paper, a hydraulic fracture propagation model is established based on the element-free Galerkin (EFG) method by introducing jump and branch enrichment functions. Based on the proposed method, three types of fracturing technology are investigated. The results reveal that the stress interference between fractures has an important impact on the propagation path. For the codirectional fracturing simultaneously, fractures propagate in a repel direction. However, the new fracture is attracted and eventually trapped by the adjacent fracture in the sequential fracturing case. For the opposite simultaneous fracturing in multiwells, two fractures with a certain lateral spacing will deflect toward each other. The effect of stress shadow should be used rationally in the optimization of construction parameters; for the single well multistage fracturing, the stage spacing should be out of stress inversion area, while for the simultaneous fracturing of multiple wells, stress inversion zones should be used to maximize communication between natural fractures. Overall, this study establishes a novel and effective approach of using MM to simulate the propagation of hydraulic fractures, which can serve as a useful reference for understanding the mechanism of hydraulic fracture propagation under various conditions.